The Effect of Mindfulness on Psychological Well-Being through Self Compassion as a Mediator for Employees - Iskandar, Natalia; Sofiah, Diah; Sari Ramadhani, Hetti (Green Publisher Indonesia, 2025)
Employee welfare is important because employees are a valuable asset of the company. Employees who have psychological well-being will contribute more to the company. The purpose of this study was to examine the relationship between mindfulness and employee psychological well-being with self-compassion as a mediator. Non-experimental quantitative research method with survey method, using google form. The research scale used was Ryff Psychological Well Being 18 items, Mindful Attention Awareness Scale (MAAS) 15 items, 12 items Short Form Neff's Self-Compassion. The data analysis technique uses path analysis with the JASP Program. The results of the study showed that all hypotheses were accepted, mindfulness had an effect (estimate=0.147) on the psychological well-being of employees. Self Compassion has an effect (estimate=0.808) on psychological well-being. Mindfulness can increase self-compassion (estimate= 0.399) so that individual interpersonal interaction improves, self-compassion is one of the potential mechanisms that link mindfulness with psychological well-being (estimate=0.323). The conclusion of this study is that there is a positive relationship between mindfulness, self-compassion and psychological well-being. Increasing mindfulness and self-compassion will improve the psychological well-being of employees. Employees who have high psychological well-being will automatically be better in their performance and performance.